Knjižnica - kulturno in socialno srce šole - Škrjanc, Petra (Knjižnica, 2019)
Purpose: The article presents a practical example of the space optimization in the school library at the Simon Gregorčič Primary School Kobarid, finished in 2016/17. It describes the historical development of the school library and lists the main reasons for the optimization of the place where the school library has been situated since 1998. By means of the design elements and the principles used before and after the place optimization, it explains the positive effects of the optimization on the place and the users alike. Due to the unsuitable spatial library design, a more ambitious vision for the quality solution of the basic spatial problem is also proposed. Methodology/approach: The article transparently describes the contextual, visual and practical viewpoints of the space optimization in the school library. Results: The processes and results of the optimization have been analysed and summarized for the first time. It is evident that the described school library space optimization can be listed among the examples of good practices in renovating the school library premises in Slovenia. Research limitations: The optimization processes were designed and executed on the basis of impartial library space flaws and subjective evaluations of the well-being by the employees and library users alike. However, although the effects of the optimization can be scientifically measured, there are no analyses of the users' well-being before the optimization process. Therefore, the results cannot be objectively compared. Originality/practical implications: The article presents the actual library space optimization and its effects on the users' well-being, as well as promotes the considerations of the qualitative and considerate design of learning and learning-supportive environment in Slovenian schools.
Keywords: kakovost; knjižnični prostori; Kobarid; osnovne šole; šolske knjižnice; uporabniki